Caries risk tests and salivary levels of immunoglobulins to Streptococcus mutans and Candida albicans in mouthbreathing syndrome patients - Koga-Ito, C. Y.; Unterkircher, C. S.; Watanabe, H.; Martins, C. A. P.; Vidotto, V; Jorge, Antonio Olavo Cardoso [UNESP] (Karger, 2003)
The aim of this study was to compare microbiological and salivary variables possibly related to caries risk in treated and untreated mouthbreathing syndrome (MBS) children and control children. Thirty control children, 30 mouthbreathers and 25 treated mouthbreathers were studied for the numbers of lactobacilli, mutans streptococci and yeasts in their saliva. Snyder's test, salivary flow and buffering capacity were also evaluated. Levels of immunoglobulins to Candida albicans and Streptococcus mutans in the saliva were quantified using ELISA. Considering the results obtained for the microbiological and salivary caries risk tests, no significant differences were observed among the proportions of patients with small/negative and high/moderate caries risk in the studied groups. The level of IgG to S. mutans was significantly higher in the treated MBS group in relation to MBS patients. on the other hand, the median anti-S. mutans IgM level was lower in the treated MBS patients than in the other groups. For the studied anti-Candida immunoglobulins, IgM level was significantly lower in the treated MBS group than in the other groups. No differences were observed for anti-S. mutans and anti-Candida IgA levels among the groups. The findings suggest that mouthbreathing cannot be considered a risk factor for dental caries. Copyright (C) 2003 S. KargerAG, Basel.
Keywords: mouthbreathing; dental caries risk tests; Candida; immunoglobulins; Streptococcus mutans